#TITLE_ALTERNATIVE# - ZUKHRUFI KOSASIH (NIM : 15312069), NAJMI
Nickel slag is one type of hazardous waste that produced in large quantities.Total production of nickel slag reaches 1 million tons/year. Nickel slag feared could cause environmental pollution problems, so it is necessary to manage and reuse the slag into a product. Nickel slag waste has the potential to be used as roadbase aggregate. In addition to reducing the amount of slag formed, the slag utilization as roadbase aggregate can also reduce the use of natural materials in large quantities. The purpose of this research is to know the characteristics,technical feasibility and leachability of nickel slag as roadbase aggregate.Characterization of nickel slag include water content, dry content, ash content,volatile content, sieving, spesific gravity, Atterberg limits, wear, lumps of clay, pH, heavy metals, and metal oxides. Heavy metals leachability of nickel slag as roadbase aggregates were analyzed by TCLP test, static and dynamic leaching test. Based on the result of physical and chemical characterization , nickel slag can be used as roadbase aggregate. There are 4 types of metal that has highest concentration, namely Ni (310.5 mg / kg), Cr (25.4 mg /kg), Co (4.1 mg/ kg) and Zn (2.45 mg / kg). The technical feasibility of slag as roadbase aggregate analyzed by Proctor and CBR (California Bearing Ratio) test. Nickel slag that its composition has met the gradation specifications has a CBR value of 108%. Referring to the specifications of Departemen Pekerjaan Umum, nickel slag can be used as grade A roadbase aggregate. TCLP test indicates that nickel slag does not have toxic characteristics because the heavy metal concentrations in leachate meets the TCLP quality standards refer to GR No. 101/2014. In general, concentrations of heavy metals contained in the leachate decreases over time on static and dynamic leaching test. The cumulative percentage of metals Ni, Cr, Co and Zn for 9 days of static leaching respectively are 0.2136 to 4.489%; 1.8882 to 2.7071%; 3.0720 to 11.546%; and 3.3918 to 5.2327%, while the dynamic leaching in the amount of 1.8874 to 3.1619%; 0.8324 to 6.3532%; 1.2295 to 3.8095%; and 2.6357 to 6.8652%.